Performing Hybrid Learning at Islamic Higher Education Institusions for Mitigating Learning Loss - Fakhri, Jamal; Sada, Heru Juabdin; Saputra, M Indra; Jamil, Syahril; Mursyidah, Dian (Jurnal Pendidikan Islam, 2023)
This research delves into the integration of hybrid learning amidst digital disruption, targeting the reduction of learning gaps within PTKI (Islamic Higher Education Institutions) context. Utilizing a blend of quantitative analysis of student data and qualitative methods including interviews, surveys, and observations across three PTKIs in South Sumatra, Indonesia, the study evaluates the effectiveness of hybrid learning in mitigating learning loss. Results highlight that the combination of virtual and traditional classroom elements through hybrid learning significantly narrows learning deficits, enhances student involvement, and fosters better academic outcomes. These findings serve as a valuable contribution to understanding hybrid learning practices specifically within PTKI settings, shedding light on its potential in addressing educational challenges amid digital advancements.